2015
DOI: 10.2118/171769-pa
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microencapsulated Phase-Change Materials To Regulate the Temperature of Oilwell Cement

Abstract: Summary During the cementing operations of oil wells, there are many situations in which it is crucial to regulate the temperature of the cement slurry during and after its placement. Limiting the temperature rise of cement-based composite materials was traditionally achieved by reducing the heat of hydration of the composite (e.g., through the use of supplementary cementitious materials or inert filling materials). However, the total amount of heat generated by a cement composite is primarily d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…FT‐IR spectra of paraffin wax, prepolymer, MPCM‐1, and MPCM‐2 are shown in Figure . For the spectra (a), the multiple absorption peaks at about 2920 and 2850 cm −1 are associated with the stretching vibration absorption peak of the saturated C─H in paraffin wax, and the absorption peak at about 1485 cm −1 signifies the flexural vibration absorption peak of C─H in paraffin wax . For the spectra (b), the strong absorption peak at about 3350 cm −1 is associated with the stretching vibration absorption peak of N─H.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…FT‐IR spectra of paraffin wax, prepolymer, MPCM‐1, and MPCM‐2 are shown in Figure . For the spectra (a), the multiple absorption peaks at about 2920 and 2850 cm −1 are associated with the stretching vibration absorption peak of the saturated C─H in paraffin wax, and the absorption peak at about 1485 cm −1 signifies the flexural vibration absorption peak of C─H in paraffin wax . For the spectra (b), the strong absorption peak at about 3350 cm −1 is associated with the stretching vibration absorption peak of N─H.…”
Section: Resultsmentioning
confidence: 99%
“…When the test temperature is less than 200°C, it was found that the mass retention rate of MPCM is 91.5%. Therefore, the leakage of paraffin wax was avoided, and the influences of melted paraffin wax on the application performances of cement slurry were also avoided …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in order to prevent the decomposition of hydrates in cementing operation, it is very important to control the heat evolution of cement slurry system. At present, the hydration heat of cement slurry system was mainly regulated by chemical and physical methods . Generally, the heat evolution of cement slurry was controlled by introducing some low hydration heat cement‐based materials, such as fly ash and slag .…”
Section: Introductionmentioning
confidence: 99%